The Sport Concussion Assessment Tool 5th Edition (SCAT5): Background and rationale. Issue 11 (26th April 2017) - Echemendia, Ruben J; Meeuwisse, Willem; McCrory, Paul; Davis, Gavin A; Putukian, Margot; Leddy, John; Makdissi, Michael; Sullivan, S John; Broglio, Steven P; Raftery, Martin; Schneider, Kathryn; Kissick, James; et al.
Abstract : This paper presents the Sport Concussion Assessment Tool 5th Edition (SCAT5), which is the most recent revision of a sport concussion evaluation tool for use by healthcare professionals in the acute evaluation of suspected concussion. The revision of the SCAT3 (first published in 2013) culminated in the SCAT5. The revision was based on a systematic review and synthesis of current research, public input and expert panel review as part of the 5th International Consensus Conference on Concussion in Sport held in Berlin in 2016. The SCAT5 is intended for use in those who are 13 years of age or older. The Child SCAT5 is a tool for those aged 5–12 years, which is discussed elsewhere.